Quantification of Lupus Anticoagulants in Clinical Samples Using Anti- β2GP1 and Anti-Prothrombin Monoclonal Antibodies - Querrec, A. Le; Arnout, J.; Arnoux, D.; Borg, J. Y.; Caron, C.; Darnige, L.; Delahousse, B.; Reber, G.; Sié, P. (Thrombosis and Haemostasis, 2001)
Quantification of lupus anticoagulant (LA) in clinical samples is hampered by the lack of a suitable standard of activity. We evaluated the use of mAbs displaying LA activity for this purpose. As most patient samples contain both β2Glycoprotein I (β2GP1) and prothrombin dependent LA, a combination of two mAbs, one of each specificity, was added to normal plasma in a concentration from 0 to 60 g/ml. Eight assay systems using different reagents and instruments were used. The calibration curves were linear for all but one, with marked differences between the responsiveness to each mAb. A panel of plasmas from 69 patients with persistent LA diagnosed using the SSCISTH criteria was tested. An antiphospholipid syndrome (APS) was present in 40, whereas 29 were asymptomatic. LA activities of individual plasmas varied between assays (p <10–4), but homogeneous subgroups were identified. In a majority of samples, LA activity displayed a prothrombin-dependent profile, with a variable contribution of β2GP1-dependent activity. The latter was associated to β2GP1 antibodies detected by solid-phase immunoassay. By using 3 dilute Russell viper venom time assays, higher LA titers were found in APS, compared to asymptomatic patients (p <0.05).
Keywords: Lupus anticoagulant; anti-β2glycoprotein 1; anti-prothrombin; monoclonal antibodies; antiphospholipid syndrome